Examining the influence of shyness on children’s helping and comforting behaviour - Karasewich, Tara A.; Hines, Cameron; Pinheiro, Sylvia G. V.; Buchenrieder, Nina; Dunfield, Kristen A.; Kuhlmeier, Valerie A. (Frontiers in Psychology, 2023)
Shy children, who tend to feel anxious around others and withdraw from social interactions, are found to be less prosocial than their not-shy peers in some studies, though not in others. To examine the contexts in which shy children may be more or less likely to engage in prosocial behaviour, we compared children’s willingness and ability to intervene during in-person tasks that differed in social engagement demands and complexity, factors that have been conflated in past research. We presented 42, 3.5- to 4.5-year-old children with prosocial problems that varied, in a 2 x 2 within-subjects design, by the type of intervention required (i.e., simple helping or complex comforting) and the source of the problem (i.e., social: within the experimenter’s personal space; or object: a target object distanced from her). Most of the children acted prosocially, with little prompting, in the two helping tasks and in the object-centered comforting task. In contrast, fewer than half of the children acted prosocially in the social-centered comforting task. Shyer children were not less likely to intervene in any of the four tasks, but they were slower to intervene in the object-centred comforting task, in which the experimenter was upset about a broken toy. Thus, providing social-centered comfort to a recently-introduced adult is challenging for young children, regardless of shyness, though shy children do show hesitancy with object-centered comforting. Further, these findings provide insights into the methodological challenges of disentangling children’s prosocial motivation and understanding, and we propose solutions to these challenges for future research.